2017
DOI: 10.1002/hec.3510
|View full text |Cite
|
Sign up to set email alerts
|

Bounding the causal effect of unemployment on mental health: Nonparametric evidence from four countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 71 publications
(126 reference statements)
3
37
2
1
Order By: Relevance
“…There are many ways to measure family SES including parental employment and its correlate, level of household income. The literature is robust in showing that unemployment can cause psychological distress in adults [26, 27] and there are mixed results for the role parental unemployment plays in child psychological distress [23, 28]. Exploration of the role of family SES through measures of income and parental employment needs to be undertaken to understand its impact on wellness for children in rural Australia.…”
Section: Introductionmentioning
confidence: 99%
“…There are many ways to measure family SES including parental employment and its correlate, level of household income. The literature is robust in showing that unemployment can cause psychological distress in adults [26, 27] and there are mixed results for the role parental unemployment plays in child psychological distress [23, 28]. Exploration of the role of family SES through measures of income and parental employment needs to be undertaken to understand its impact on wellness for children in rural Australia.…”
Section: Introductionmentioning
confidence: 99%
“…So far, however, the majority of empirical studies have yielded only correlational evidence about this issue. On the other hand, related research emphasizes that health and well-being suffers from underemployment and particularly unemployment (e.g., Aghion et al, 2016;Cygan-Rehm et al, 2017;Winkelmann and Winkelmann, 1998;Wunder and Heineck, 2013), as well.…”
Section: Introductionmentioning
confidence: 99%
“…There is ample empirical evidence that mental health is causally determined by unemployment (e.g., Stauder 2019, Cygan-Rehm et al 2017, Gebel and Voßemer 2014, although some authors have also reported null effects (e.g., Böckerman andIlmakunnas 2009, Schmitz 2011). However, the matter of which causal mechanisms are triggered after job loss and lead to negative mental health largely remains an open question.…”
Section: Theoretical Considerations and Hypothesesmentioning
confidence: 99%